Effect of maternal and post-weaning dietary chitosan oligosaccharide supplementation on reproductive performance of sow and gut growth and development in offspring - Fang, Tingting; Yao, Ying; Tian, Gang; Zheng, Ping; Yu, Jie; Yan, Hui; Pu, Junning; Yu, Bing (Frontiers in Veterinary Science, 2025)
This study investigated the effects of dietary chitosan oligosaccharide (COS) in sows on the reproductive performance and milk composition of sows, as well as the intestinal growth and development of piglets. A total of forty pregnant sows (average parity = 4) at day 90 of gestation were randomly divided into two groups and fed a basal diet (CONm, n = 20) or a diet supplemented with 100 mg/kg COS (COSm, n = 20) from late gestation to lactation. At 24 days of age, a 2 × 2 factorial treatment arrangement was employed with two independent factors: the sow diet and the piglet diet. The piglets selected from the same litter of sows fed CONm or COSm were assigned to receive either a control diet (CONp, n = 6) or a diet containing 100 mg/kg COS (COSp, n = 6) for 14 days. Maternal COS supplementation shortened the weaning-to-estrus interval and improved milk composition, up-regulated jejunal mRNA expressions of CLDN3, SDCBP2, LDHA, MAP2K1, and PCK1, ileal concentrations of IL-10 and IFN-γ in 2-days old suckling piglets (p < 0.05); and enhanced plasma TG level, jejunal mRNA expressions of CLDN7 and HNF4A, ileal concentrations of IL-10 and CD163 mRNA expressions in 24-days old suckling piglets (p < 0.05). In 38-days old weaning piglets, maternal COS enhanced the ratio of Lactobacillus spp.-to-Escherichia coli, butyrate, and propionate concentrations in cecal digesta, as well as decreased the concentrations of IL-10 and IFN-γ in ileal mucosa (p < 0.05), and the concentration of Escherichia coli (p < 0.05) in cecal digesta. Meanwhile, COS supplementation in weaned piglets increased the jejunal mRNA level of CD163, and cecal acetate, propionate, and total SCFA contents (p < 0.05). There were interaction effects between dietary COS in sow and dietary COS in piglet on ileal density, jejunal crypt depth and jejunal mTOR expression (p < 0.05). These results indicated that maternal COS intervention can enhance the reproductive performance and milk composition in sows, while improving intestinal growth and immunity parameters of suckling piglets. Furthermore, supplementing both sows and piglets with COS appeared to be a more effective way to promote gut growth in weaning piglets.